Installation and evaluation of autonomous solar dryer for potato drying in Tarma - Camayo Lapa, Bécquer Frauberth; Quispe Solano, Miguel Angel; Huamán De La Cruz, Alex Ruben; Condezo Hurtado, David Elvis; Massipe Hernández, Juan Raúl; Landa Guadalupe, Liz Evelyn (Revista Mexicana de Ciencias Agrícolas, 2020)
In this work, an autonomous and automated solar dryer has been developed to dry potatoes in the town of Tarma at an altitude of 3 040 m in July 2019, which has a solar collector with two reflectors, a drying chamber with a capacity of 20 kg, photovoltaic panel and a control system. The thermal behavior of the no-load solar dryer was studied, achieving increases in the temperature in the drying chamber of up to 50.7 ±7 °C with solar radiation of 880 ±144 W m-2 h-1. The effect of pretreatment was evaluated with two concentrations of sodium bisulfite (0.02% and 0.03%) and three drying temperatures (50 °C, 55 °C and 60 °C) to evaluate the physical (L*), physical-chemical characteristics (acidity, pH) and chemicals (humidity and ash). The results showed a reduction of 70% of the water having a final humidity between 12.56% to 13.85%. Likewise, no significant difference (p> 0.05) was found between the physical, physicochemical, and chemical characteristics at the different bisulfite concentrations and drying temperatures of the Yungay potato. These potato quality parameters are in accordance with the Peruvian standard NTP 011.119 ‘potato and its derivatives: potato, definitions and requirements’, which offers an efficient alternative to dehydrated agricultural products.
Keywords: automated; autonomous solar dryer; indirect solar drying; potato